Children's headache through drawings - Vincenzo Raieli; Edvige Correnti; Giuseppe Santangelo; Federica Cernigliaro; Salvatore Lo Cascio; Simona Rena Tomasino; Carola Meo (Publiediting, 2023)
Headache is the most common neurological disorder in the paediatric population. The diagnosis of headache in children can be complicated by the presence of different clinical phenotypes than in adults and by the difficulty of young patients in verbally communicating their symptoms. Therefore, drawings in children can be of great value in the diagnosis of different types of headache. In addition, children project their unconscious into drawings, so features such as colour, size, body parts, light, darkness, line thickness, different shapes and various details can provide important information in clinical practice. This article provides a brief literature review and description of some clinical cases with the aim of encouraging the use of drawing in paediatric headache clinical practice. The literature since 1983 provides us with some examples of the accuracy and effectiveness of 'artistic' diagnosis as an aid to clinical diagnosis. Our review of these studies confirms the importance of this tool in clinical practice. We analysed the clinical cases of two of our young patients: a 6-year-old girl with migraine and cyclic vomiting, and a 7-year-old girl with cranial autonomic symptoms (CAS). These girls were asked to make drawings of their pain and their feelings about pain. Data from the literature suggest drawing as an additional aid in both the diagnostic process and follow-up, as drawing is an effective, pleasant, inexpensive and easy-to-use tool. Future perspectives include drawing as a tool to assess the effectiveness of therapy and quality of life in our young patients.